Socio-Cultural Interaction of TikTok Users on Stock Investment Content: A Netnographic Study - Prasetianingsih, Leni; Sokarina, Ayudia (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research is a netnographic study that discusses socio-cultural interactions in stock investment content on TikTok. This research aims to understand how socio-cultural interactions shape TikTok users' views and behaviors in stock investment content. Data collection uses a lacer/passive approach through a single Tiktok platform. The type of data in this study is archival data in the form of screenshots of comments and field notes containing personal reflections of researchers. Analysis uses the netnography method, namely Coding, Noting, and Abstracting. The results of the study include 6 main findings, namely, Interest in starting and learning stocks, Various investment interests and decisions, Obstacles and challenges in starting stock investment, Various Opinions / views on stock investment, Sharing investment information and experiences, and Appreciation of information. This research illustrates how cultural interactions on TikTok shape users' investment behavior. It can help policy makers, academics, and financial practitioners to understand investment trends in the younger generation. It also highlights the importance of financial literacy and cultural values in investment.